Aktivitas Antioksidan, Karakteristik Fisik, Dan Sensoris Yogurt Beku Kecambah Kacang Merah Dengan Variasi Penambahan Ekstrak Kulit Buah Naga Merah - Bherta Agil Dhela Kusuma; Siti Aminah; Wikanastri Harsoelistyorini (Jurnal Pangan dan Gizi, 2022)
Frozen bean sprouts yogurt is a probiotic drink made from fermented vegetable milk that has a consistent texture and is synonymous with sour taste. In the fermentation process of yogurt, lactose is broken down from lactic acid bacteria into lactic acid. One of the innovations is to improved quality of yogurt by adding variations in the addition of red dragon leather extract which contains polyphenols and antioxidants. The purpose of this study was to determine the antioxidant activity, physical and sensory characteristics with the addition of red dragon fruit peel extract. This study used a completely randomized design (CRD) with 5 treatments with 5 replications. The treatment for the addition of dragon leather extract used was (0; 1; 3; 5; and 7 percent). The analysis in this research is analysis of antioxidant activity, physical characteristics, and sensory. The results showed that the addition of red dragon leather extract significantly different from antioxidants and physical characteristics. Meanwhile, the sensory properties were not significantly different. The best treatment was obtained at a concentration of 5% which has sensory properties (4.02), pH (4.34), viscosity (4006 mPas) and antioxidant activity of 26.17% RSA.